Āl-Murāqābāh wā āt-Tāqwīm ‘ālā Bārnāmījī āl-Lughāh āl-‘Ārābīyyāh bīī Mārkāzī āt-Tānwīr līī āl-Lughāt - Imroatul Muthoharoh; Durrotun Nashihah; Zakiyah Arifa; Nur Kholid; Muhammad Fajrul Rs (Mantiqu Tayr: Journal of Arabic Language, 2024)
The aim of this research to find out and explain how supervision and evaluation management occurs in the Arabic language learning program of At-Tanwir Language Center. The background of this research is At-Tanwir Language Center (ALC) as an extracurricular organization of Arabic language learning for At-Tanwir Islamic Junior and Senior High School students who have an interest and talent in Arabic language. This research used descriptive qualitative research that used interview, observation and documentation techniques for collecting the data. The results of this research showed that supervision of the ALC learning program is internal supervision, active and passive supervision as well as preventive and repressive supervision. Carried out by ALC supervisors through the ALC chair, including active supervision by directly observing the program in progress, and passive supervision by viewing teacher and student attendance lists, teaching journals, and other learning tools. As well as preventive and repressive supervision which carried out to plan and implement the program, it runs effectively and efficiently and this supervision also carried out after learning activities and carried out in order to find out the results of program implementation and evaluate the deviations. Meanwhile, the program evaluation carried out continuously once a month. It also carried out at the end of each learning semester. As for the reporting learning outcomes, ALC divides it into 2 parts, namely short-term and long-term evaluation. This supervision and evaluation carried out for continuous improvement that will be carried out every year to improve the program. Through this research, the monitoring and evaluation management process at course institutions, especially Arabic, is known. As for suggestions for future researchers, they can continue research on the influence of supervision and evaluation on the development of an institution.